3D Seismic Tomography Imaging of Taiwan Substructure - Diah Ningrum, Susi Anggraini; Santosa, Bagus Jaya (Institut Teknologi Sepuluh Nopember, 2015)
Taiwan has a high rate of crustal deformation and a strong seismic activity. Taiwan is located on the convergent boundary between the Eurasian and the Philippine Sea plates. Seismic tomography is an imaging technique that uses seismic waves to create three-dimensional images of Earth’s interior. We use the earthquake of M > 4.7 and occurred in the period of 1 January 2009 to 31 December 2010. The data processing steps of seismic tomography are picking of P and S wave using SeisGram2K60, hypocenter relocation using Hypo71, and tomography inversion using LOTOS-12. The result shows that there is high Vp and Vs in the eastern Taiwan that represent the western boundary of Philippine Sea Plate with Longitudinal Valley.